Building gender-responsive climate security: Inside CGIAR’s new training module - Kadry, Salma; Campbell, Raramai; Caroli, Giulia; Maviza, Gracsious; Takaindisa, Joyce; Penel, Charlotte; Palou, Nohelia; Synnestvedt, Thea; Vaselli, Alessandra; Jaskolski, Martina; Ramos, Cristina (2025)
This blogpost provides a gateway to multiple open access training sessions that form part of a plug and play training course on gender, inclusion, and climate security